Gen Pengendali Sifat Ketahanan Penyakit Blas (Pyricularia grisea Sacc.) pada Spesies Padi Liar Oryza rufipogon Griff. dan Padi Budi Daya IR64 - Dwinita Wikan Utami; Sugiono Moeljopawiro; Hajrial Aswidinnoor; Asep Setiawan; Ida Hanarida (Jurnal AgroBiogen, 2005)
Improvement of rice for durable resistance rice blast is difficult due to the complexity of the inheritance of resistance. As study was conducted to analyze blast resistance in rice using two different approaches, i.e., blast QTL mapping and comparison of resistance spectrum and genetic control. The blast QTL mapping was done using an interspesific population originated from backcrossing between a wild rice, Oryza rufipogon, and a cultivated rice, IR64. Comparison of resistance spectrum and genetic control was based on phenotypic reactions. Results of the experiment showed that based on the blast QTL mapping, genes Pirf2-1(t) and Pir2-3(t) were mapped on chromosome 2. Gene Pirf2-1(t) was isolated from chromosome 2 of O. rufipogon and coding for resistance to P. grisea race 001, while gene Pir2-3(t), which was isolated from rice cultivar IR64, was coding for resistance to P. grisea race 173. Based on the resistance spectrum, O. rufipogon has a non-race specific resistance. Gene Pirf2-1(t) on O. rufipogon contributed a dominant mode of resistance to blast which was affected by a duplicate epistasis. The other gene, Pir2-3(t) contributed an additive mode of resistance which was affected by a complementary epistasis.